2013
DOI: 10.1111/1755-0998.12181
|View full text |Cite
|
Sign up to set email alerts
|

A new multiplex SNP genotyping assay for detecting hybridization and introgression between the M and S molecular forms of Anopheles gambiae

Abstract: The M and S forms of A. gambiae have been the subject of intense study, but are morphologically indistinguishable and can only be identified using molecular techniques. PCR-based assays to distinguish the two forms have been designed and applied widely. However, the application of these assays towards identifying hybrids between the two forms, and backcrossed hybrids in particular, has been problematic as the currently available diagnostic assays are based on single loci, and/or are located within a multi-copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 48 publications
3
55
1
Order By: Relevance
“…A few studies have used multiple restriction fragment length polymorphism assays and/or mismatch primer-based SNP assays to genotype one SNP in each of the three (X, 2L, and 3L) islands of divergence (26,36). We extended this approach with the development of the DIS assay (35) to describe A. gambiae populations throughout West Africa ( Fig. 1 and SI Appendix, Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have used multiple restriction fragment length polymorphism assays and/or mismatch primer-based SNP assays to genotype one SNP in each of the three (X, 2L, and 3L) islands of divergence (26,36). We extended this approach with the development of the DIS assay (35) to describe A. gambiae populations throughout West Africa ( Fig. 1 and SI Appendix, Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…1 and SI Appendix, Table S3). The DIS assay includes 7 SNPs spanning 4.4 Mbp on the X chromosome, 5 spanning 2.2 Mbp on chromosome 2L, and 3 spanning 117 kb on chromosome 3L (35). Genotypes at these 15 SNPs were used to designate individuals as M form, S form (homozygous for form-specific alleles at a minimum of 13 of the 15 SNPs), F 1 hybrids (heterozygous at all 15 SNPs), and backcross (individuals with mixed M, S, and heterozygous genotypes at 3 or more SNPs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA was extracted using a DNeasy extraction kit (Qiagen). Species determination of mosquitoes from the A. gambiae complex were made with the combination of species diagnostic assays ( Fanello et al , 2002; Favia et al , 2001; Santolamazza et al , 2008; Scott et al , 1993) and a divergence island SNP (DIS) genotyping assay ( Lee et al , 2014) while other species were identified by morphology.…”
Section: Methodsmentioning
confidence: 99%